2017
DOI: 10.1080/01480545.2017.1320407
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation enzyme activities and phase I metabolites analysis inLitopenaeus vannameifollowing intramuscular administration of T-2 toxin

Abstract: T-2 toxin (T-2) is a type-A trichothecene produced by Fusarium that causes toxicity to animals. T-2 contamination of grain-based aquatic feed is a concern for the industries related to edible aquatic crustacean species such as the shrimp industry because it can lead to serious food safety issues. T-2, its metabolites, and selected phase I (EROD, CarE) and phase II (GST, UGT, SULT) detoxification enzymes in hemolymph and tissues were monitored at 0, 5, 10 15, 30, 45, and 60 min following T-2 intramuscular admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, CYP1A1 in human [ 34 ]; CYP3A46, CYP3A29, and CYP3A22 in pig [ 94 , 95 , 96 ]; and CYP1A5 and CYP3A37 in chicken [ 97 , 98 ] mainly convert T-2 to 3′-OH-T-2 and HT-2 to 3′-OH-HT-2 [ 145 ]. The carboxylesterase is also an important phase I enzyme, contributing to the rapid metabolism of T-2 to HT-2 [ 100 ]. A recent study revealed that cholic acid supplementation promotes the T-2 metabolism through activation of the farnesoid X receptor, which was found to have significantly increased the expression of CYP3A37 [ 99 ].…”
Section: Biotransformation Of Mycotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CYP1A1 in human [ 34 ]; CYP3A46, CYP3A29, and CYP3A22 in pig [ 94 , 95 , 96 ]; and CYP1A5 and CYP3A37 in chicken [ 97 , 98 ] mainly convert T-2 to 3′-OH-T-2 and HT-2 to 3′-OH-HT-2 [ 145 ]. The carboxylesterase is also an important phase I enzyme, contributing to the rapid metabolism of T-2 to HT-2 [ 100 ]. A recent study revealed that cholic acid supplementation promotes the T-2 metabolism through activation of the farnesoid X receptor, which was found to have significantly increased the expression of CYP3A37 [ 99 ].…”
Section: Biotransformation Of Mycotoxinsmentioning
confidence: 99%
“…The transformation of T-2 to T-2-3-glucuronide and HT-2 to HT-2-3-glucuronide and HT-2-4-glucuronide occurs in liver microsomes of rats, mice, pigs and humans [ 155 ]. The activities of GSTs and sulfotransferases can be also attributed to the conjugation reaction as a response to T-2 exposure [ 100 , 101 ].…”
Section: Biotransformation Of Mycotoxinsmentioning
confidence: 99%
“…) and one of the most toxic mycotoxins . T‐2 contamination is widespread in animal feed, including shrimp feed . In shrimp, T‐2 mostly affects protein synthesis by causing apoptosis and inhibiting protein synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Phase II metabolism of T-2 toxin involves conjugation reactions with endogenous molecules such as glutathione, sulfate, and glucuronic acid, leading to the formation of water-soluble metabolites that are more readily excreted from the body [40]. Glutathione S-transferases catalyze the conjugation of T-2 toxin with GSH to form glutathione conjugates, which are subsequently metabolized to mercapturic acid derivatives and excreted in the urine and feces.…”
Section: Metabolism Of T-2 Toxin In Poultrymentioning
confidence: 99%